2022
DOI: 10.4143/crt.2021.585
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impairments in the Mental Health, Depression and Anxiety Related to the Viral Epidemic, and Disruption in Healthcare Service Utilization among Cancer Patients in the COVID-19 Pandemic Era

Abstract: Literature is scarce regarding cancer care utilization during the massive outbreak of coronavirus disease 2019 in the Republic of Korea. We investigated functional impairments in mental health and their relationships with depression, anxiety regarding the viral epidemic, and disruptions in healthcare service utilization among cancer patients in the COVID-19 pandemic era. Materials and MethodsWe used an online survey with questions related to the disturbances faced by patients with cancer in utilizing healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 31 publications
1
37
0
1
Order By: Relevance
“…The instrument was developed using a sample that included students, cardiac, and chronic pain patients. Recent studies conducted during the COVID-19 pandemic have used this instrument to explore resilience across countries and populations ( Ben Salah et al, 2021 ; Kaur et al, 2021 ; Kim et al, 2021 ), and have explored its associations with depression, as measured by the PHQ-9. To measure self-perceived social support, we designed two 4-point Likert-type scales (from “strongly disagree” to “strongly agree”).…”
Section: Methodsmentioning
confidence: 99%
“…The instrument was developed using a sample that included students, cardiac, and chronic pain patients. Recent studies conducted during the COVID-19 pandemic have used this instrument to explore resilience across countries and populations ( Ben Salah et al, 2021 ; Kaur et al, 2021 ; Kim et al, 2021 ), and have explored its associations with depression, as measured by the PHQ-9. To measure self-perceived social support, we designed two 4-point Likert-type scales (from “strongly disagree” to “strongly agree”).…”
Section: Methodsmentioning
confidence: 99%
“…12 In the general cancer population, disruption of access to health care predicted depression, anxiety, and low resilience. 13 Oncologists are often called to fill the role of psychotherapists for patients with cancer, assisting them in modifying behaviors, cognition, and emotions, as they navigate the turmoil of their diagnosis. 14 The increased uncertainty about provision of cancer-related care combined with reduced access to the oncologist as a source of support has created a potential for imbalance in the physiologic equilibrium of ovarian cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that a higher level of distress from the COVID-19 pandemic correlated with a higher level of anxiety and fear in patients with cancer ( 13 ). Moreover, the distress stemmed from the pandemic itself, as well as from the interruptions in cancer care services ( 14 ), which could delay the diagnosis or proper management of cancer. Indeed, the fear and anxiety of contracting COVID-19 led to a greater risk of the postponement of scheduled chemotherapy ( 15 ), and the refusal of cancer-related procedure and surgery ( 16 ).…”
Section: Introductionmentioning
confidence: 99%